Size-dependent characteristics of electrostatically actuated fluid-conveying carbon nanotubes based on modified couple stress theory - Fakhrabadi, Mir Masoud Seyyed; Rastgoo, Abbas; Ahmadian, Mohammad Taghi (Beilstein Journal of Nanotechnology, 2013)
The paper presents the effects of fluid flow on the static and dynamic properties of carbon nanotubes that convey a viscous fluid. The mathematical model is based on the modified couple stress theory. The effects of various fluid parameters and boundary conditions on the pull-in voltages are investigated in detail. The applicability of the proposed system as nanovalves or nanosensors in nanoscale fluidic systems is elaborated. The results confirm that the nanoscale system studied in this paper can be properly applied for these purposes.
Keywords: carbon nanotubes (CNT); electrostatic actuation; fluid flow; modified couple stress theory